Pattern of dermatophytes among skin, hair, and nail specimens in a tertiary care hospital of Lahore (Journal of Fatima Jinnah Medical University, 2022)
Background: Dermatophytes are considered to be the most common cause fungal of infections globally. The geographical distribution of these fungi varies from region to region. The aim of this study was to isolate and determine the frequency and variety of various dermatophytes from clinically suspected cases of dermatophytoses.Patients and methods: This was a descriptive study carried out at the Department of Microbiology, Post graduate Medical Institute, Lahore over a period of nine months from July 2013 till March 2014. Nonprobability convenient sampling was used. One hundred clinically suspected cases of dermatophytosis were selected for this study. Specimen of skin, hair and nail were taken from patients and were evaluated by both microscopic examination and culture. Dermatophytes were identified based on the colony morphology as well as microscopic arrangement of macroconidia and microconidia. Data was collected and entered in Statistical Package for the Social Sciences (SPSS) version 20.0.Results: Out of a total of 100 patients, 48 were male and 52 were female. The majority of cases were from the age group of 31-40 (25%) followed by less than 10 years (18%). Out of hundred patients, 59 (59%) were positive on direct microscopy with KOH wet mount. Fungal culture was positive in 56 (56%) cases. Out of these 56 positive cultures, twenty-three were identified as dermatophyte species. Trichophyton rubrum was the commonest isolate. Other dermatophyte species isolated were Trichophyton mentagrophytes, Trichophyton verrocosum, Microsporum canis, Trichophyton tonsurans, and Microsporum audonii.Conclusion: Studying the pattern of dermatophyte species is necessary as it helps in the early diagnosis and treatment of dermatomycoses. This study identified Trichophyton rubrum as the commonest etiological agent of dermatophytoses.
Keywords: Dermatophytes; KOH mount; Fungal culture; Trichophyton rubrum